YouTube : illegally tracking children's data - Gordon, Zachary, (SAGE Business Cases., 2019)
Google subsidiary, YouTube, has collected data of children users without the consent of parents and then sold the data to advertisers. The Federal Trade Commission fined Google $170 million in what was the largest fine in Google's history. Absent a plausible public explanation, YouTube and its parent company risk anger and alienation from investors, application users, parents groups, and perhaps further regulatory oversight from the Congress of the United States.